Verfassungsschutzbericht 1997 - Hrsg. Bundesministerium des Innern. (Bundesministerium des Innern, 1998)
Available on the Internet at http://www.bundesregierung.de/02/0201/innen/vsber97/Includes indexes, p. 255-268.